Analyzing the Impact of Natural Resource Depletion and Government Effectiveness on Happiness in Selected Oil-Exporting Countries - Ibrahim Askar , Wafaa; Hafezi, Bahar; Abdullah Salman, Ahmed; Sharifi Renani, Hossein (Business, Marketing, and Finance Open, 2025)
The concept of happiness is a subject of study among economists. Happiness can be improved by economic, social, and institutional factors. Natural resource depletion, as an economic factor that also influences institutional indicators, can impact happiness. Therefore, this study examines whether natural resource depletion, considering government effectiveness, affects the happiness of people in oil-exporting countries. To this end, the Pooled Mean Group (PMG) model was applied to seven selected oil-exporting countries over the period from 2006 to 2023. The results indicate that the effect of natural resource depletion on happiness follows an inverted U-shape. In other words, initially, as the extraction of natural resources increases, higher oil revenues lead to improved individual incomes and, consequently, greater happiness. However, with further resource extraction, the depletion of natural resources and the increasing rent from these resources result in a long-term decline in happiness. Furthermore, government effectiveness has a positive long-term impact on happiness. Given that the effect of Gross Domestic Product (GDP) on happiness also follows an inverted U-shape in the long run, the Easterlin paradox is confirmed.